Peran Media Sosial Dalam Knowledge Management Pada Organisasi: A Literature Review - Najma Choirun Nisa; Nadya Ilma Pratiwi; Awidya Chandradewi (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Writing this research aims to examine the role of social media in the management of knowledge or knowledge management. We use a literature review by applying a tool available in the literature review called PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis). PRISMA consists of a number of items that must be considered and reported in a literature review, from the planning stage to the presentation of results. The results of the research we have done show that knowledge management has an important function in managing knowledge in an organization. With the existence of facilities for sharing, interacting, broad access to knowledge, collaboration facilities, offering sophisticated search tools on social media which when used optimally can help an organization to manage knowledge. Overall, social media has both positive and negative impacts so its use must be exercised with caution in terms of privacy, information security and ethics. Thus, this study aims to conduct a comprehensive literature review on the role of social media in knowledge management.